Adjunct use of mouth rinses with a sonic toothbrush accelerates the detachment of a Streptococcus mutans biofilm: an in vitro study - Tatsuya Ohsumi; Shoji Takenaka; Yuuki Sakaue; Yuki Suzuki; Ryoko Nagata; Taisuke Hasegawa; Hayato Ohshima; Yutaka Terao; Yuichiro Noiri (BMC, 2020)
Abstract Background The aim of this in vitro study was to examine the possible enhancement of the biofilm peeling effect of a sonic toothbrush following the use of an antimicrobial mouth rinse. Methods The biofilm at a noncontact site in the interdental area was treated by sound wave convection with the test solution or by immersion in the solution. The biofilm peeling effect was evaluated by determining the bacterial counts and performing morphological observations. A Streptococcus mutans biofilm was allowed to develop on composite resin discs by cultivation with stirring at 50 rpm for 72 h. The specimens were then placed in recesses located between plastic teeth and divided into an immersion group and a combination group. The immersion group was treated with phosphate buffer, chlorhexidine digluconate Peridex™ (CHX) mouth rinse or Listerine® Fresh Mint (EO) mouth rinse. The combination group was treated with CHX or EO and a sonic toothbrush. Results The biofilm thickness was reduced by approximately one-half compared with the control group. The combination treatment produced a 1 log reduction in the number of bacteria compared to the EO immersion treatment. No significant difference was observed in the biofilm peeling effect of the immersion group compared to the control group. Conclusions The combined use of a sonic toothbrush and a mouth rinse enhanced the peeling of the biofilm that proliferates in places that are difficult to reach using mechanical stress.